The Effect Of Store Atmosphere And Service Quality On Customer Satisfaction At Simetri Coffee Roaster, Bekasi City, West Java - Jasmani Jasmani; Triyadi Triyadi; Ahmad Lutfi; Denok Sunarsi (STEBIS Bina Mandiri, 2026)
This study aims to determine the effect of store atmosphere and service quality on consumer satisfaction at Simetri Coffee Roaster, Bekasi City, West Java. The method used is explanatory research with analysis techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study show that store atmosphere has a significant effect on consumer satisfaction with a contribution of 45.2% and the hypothesis test obtained t count > t table or (8.989 > 1.984). Service quality has a significant effect on consumer satisfaction with a contribution of 42.4% and the hypothesis test obtained t count > t table or (8.500 > 1.984). Store atmosphere and service quality simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 5.849 + 0.450X1 + 0.409X2 obtained with an influence contribution of 60.6%, and the hypothesis test obtained F count > F table or (74.727 > 2.700).